A CASE OF DELAYED DIAGNOSIS OF SEVERE B. BURGDORFERI MENINGO-ENCEPHALITIS. (29th November 2012) - Cheripelli, B; Hall, GL
Abstract : An early diagnosis of neuroborreliosis is imperative, as full recovery may not be achieved with delayed treatment. The diagnosis may be delayed due to atypical presentation of this rare condition. We report a case of 44-year-old farmer with a delayed diagnosis of a severe meningo-myelitis secondary to B.burgdorferi infection. He presented with a 21-month history of progressive limb weakness, and several weeks history of headaches. Complicating his presentation, at the onset he reported six episodes, each lasting few minutes to half an hour of sudden onset right sided weakness. MRI brain showed a small infarct in left side of medulla. He was commenced on secondary prophylaxis for stroke. However, his symptoms deteriorated prompting admission to a neurology ward. Examination showed asymmetric spastic quadriparesis. MRI showed a high signal cord-expanding lesion in cervical cord with meningeal enhancement extending to posterior fossa. CSF showed a lymphocytic pleocytosis (WBC 250, Lymphocytes 94%), raised protein (4.8 g/dl), and low glucose of 0.2 mmol/l (serum glucose 4.7 mmol/l). Serum B.burgdorferi IgG C6 antibody, and IgG immunoblotting were positive. CSF B. burgdorferi IgG immunoblotting was strongly positive. CSF cultures were negative for TB. He received 1-month course of Intravenous Ceftriaxone. Although repeat MRI had improved, the patient was severely disabled. The unusual TIA like episodes, which may have been coincidental and the initial MRI have led to the delay in diagnosis. Early recognition and treatment of neuroborreliosis can prevent significant disability.